2013
DOI: 10.1002/phar.1322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Immunoglobulin G–Specific Enzyme‐Linked Immunosorbent Assay on the Management of Heparin‐Induced Thrombocytopenia

Abstract: Use of an IgG-specific PF4 ELISA was associated with a lower rate of positive PF4 test results. Direct thrombin inhibitor prescribing was also significantly lower during the time period where the IgG-specific PF4 ELISA was used, with no significant differences noted in safety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This characteristic can make results from polyvalent ELISAs misleading, since polyvalent results have good negative predictive value for HIT, but may not have good positive predictive value due to potential identification of clinically irrelevant antibodies. 21,22 In clear positive samples, we observed good agreement between the two types of ELISAs. It should be noted that even IgG-specific ELISAs have imperfect positive predictive value because they indicate only that antibodies are present, but cannot demonstrate the platelet activating properties of the antibodies.…”
Section: Discussionsupporting
confidence: 61%
“…This characteristic can make results from polyvalent ELISAs misleading, since polyvalent results have good negative predictive value for HIT, but may not have good positive predictive value due to potential identification of clinically irrelevant antibodies. 21,22 In clear positive samples, we observed good agreement between the two types of ELISAs. It should be noted that even IgG-specific ELISAs have imperfect positive predictive value because they indicate only that antibodies are present, but cannot demonstrate the platelet activating properties of the antibodies.…”
Section: Discussionsupporting
confidence: 61%
“…Cycle 3 found that extended VTE prophylaxis was not effective, and heparin‐induced thrombocytopenia (HIT) emerged as a concerning adverse effect . In cycle 4, HIT diagnosis and management was explored, leading to an assessment and change in the diagnostic assay that was then evaluated in cycle 5 . A diverse group (pharmacists, physicians, nurses, laboratory staff) participated in this MUE, and each cycle led to a follow‐up cycle, all with continuous measurements and practice changes.…”
Section: Medication Use Evaluation Modelsmentioning
confidence: 99%
“…This time frame was chosen to include only results from an IgG antiheparin-PF4 ELISA, as our institution had transitioned from a non-Ig-specific antiheparin-PF4 ELISA prior to 2012. 6 The major endpoint was to assess the incidence of positive SRA results in patients with antiheparin-PF4 ELISA values !0.4 OD units when compared to patients with antiheparin-PF4 ELISA values greater than or equal to 0.8 and 1.0 OD units. We also sought to explore the ability of each antiheparin-PF4 ELISA threshold to correctly classify patients according to SRA results by calculating the sensitivity, specificity, PPV, NPV, and accuracy.…”
Section: Methodsmentioning
confidence: 99%